2023
DOI: 10.1523/jneurosci.1506-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral Striatum is a Bottleneck for Responding to Task-Relevant Stimuli in a Learned Whisker Detection Task in Mice

Abstract: A learned sensory-motor behavior engages multiple brain regions, including the neocortex and the basal ganglia. How a target stimulus is detected by these regions and converted to a motor response remains poorly understood. Here, we performed electrophysiological recordings and pharmacological inactivations of whisker motor cortex and dorsolateral striatum to determine the representations within, and functions of, each region during performance in a selective whisker detection task in male and female mice. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
3
2
0
Order By: Relevance
“…We show that different cortical and subcortical regions contain relevant predictive information about neural activity in the SSp-bfd. Interestingly, these regions are consistent with previous accounts of the mouse whisker system 2225 , and the anatomical connections between these regions 29,31 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We show that different cortical and subcortical regions contain relevant predictive information about neural activity in the SSp-bfd. Interestingly, these regions are consistent with previous accounts of the mouse whisker system 2225 , and the anatomical connections between these regions 29,31 .…”
Section: Resultssupporting
confidence: 91%
“…We found that the neural population activity in the SSp-bfd could be predicted with a high accuracy from the BOLD fMRI activity in different regions of the mouse brain. This finding is consistent with previous studies in that regions implicated in whisker stimulation 2225 , as well as anatomically connected areas 29,31 contained a high level of information about the local neural activity in the SSp-bfd. Using our method, future studies can now investigate whether regions across the brain contain distinct predictive information about diverse local neuronal subsets that differ in their genetics or projection specificity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Experimental protocols have been approved by the IACUC of University of California, Riverside. The behavioral dataset used here includes studies that have been previously reported (Aruljothi et al, 2020; Marrero et al, 2022; Zareian et al, 2023; Zareian et al, 2021; Zhang & Zagha, 2023). Wild type (C57BL/6J, JAX #000664; BALB/cByJ, JAX #001026), transgenic (Snap25-2A-GCaMP6s-D, JAX #025111; Thy1-ChR2-YFP, JAX #007612; VGAT-ChR2-EYFP, JAX #014548), and virus-injected adult male and female mice were included in the behavioral learning data.…”
Section: Methodsmentioning
confidence: 99%
“…73,81,82,83,84,85,86 While some studies treat striatal inputs as a uniform entity, 87,88 they have been shown to differ anatomically, 73,74,76 functionally, 89,90 and behaviorally. 89,91,92 Thus, the specific cortical and thalamic origin of striatal inputs likely has significance for understanding how the striatal circuitry integrates sensorimotor information to modulate behavior.…”
Section: Introductionmentioning
confidence: 99%